2010
DOI: 10.4067/s0718-40262010000500014
|View full text |Cite
|
Sign up to set email alerts
|

Aneurisma verdadero en arteria ciática persistente: Caso clínico

Abstract: Persistent sciatic artery aneurysm. A case reportWe report the case of a 71 years old female patient, who had a partially thrombosed true aneurysm in a persistent sciatic artery (PSA), treated in the Surgery Department of Hospital Dr. Eduardo Pereira of Valparaíso. The sciatic artery arises from the umbilical artery and during early embryological state is the main blood supply of the lower limbs. Later, the superfi cial femoral artery appears with the subsequent progressive involution of the sciatic artery. PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
(16 reference statements)
0
6
0
4
Order By: Relevance
“…Thrombosis is a common causal pathology for three widespread cardiovascular syndromes: acute coronary syndrome (ACS), venous thromboembolism (VTE), and strokes [5,6]. Furthermore, the latest statistical study from the Global Burden of Diseases, Injuries and Risk Factors (GBD) showed that 25% of people worldwide die from thrombosis related events [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombosis is a common causal pathology for three widespread cardiovascular syndromes: acute coronary syndrome (ACS), venous thromboembolism (VTE), and strokes [5,6]. Furthermore, the latest statistical study from the Global Burden of Diseases, Injuries and Risk Factors (GBD) showed that 25% of people worldwide die from thrombosis related events [7].…”
Section: Introductionmentioning
confidence: 99%
“…En el tipo completo(63-79% de los casos), la arteria ciática persistente se continúa con la arteria poplítea que representa el suministro dominante para los miembros inferiores, mientras que la arteria femoral superficial es hipoplásica y ofrece solo los vasos colaterales de la extremidad inferior. En el tipo incompleto (aproximadamente el 20% de los casos), la arteria ciática persistente es hipoplásica y la arteria femoral superficial es el principal suministro de sangre de la extremidad inferior 5 . El caso de nuestro paciente se trata de una ACP completa.…”
Section: Discussionunclassified
“…Una ACP asintomática no requiere tratamiento, pero debe ser controlada en forma periódica de por vida a través de métodos no invasivos para disminuir el riesgo de complicaciones tromboembólicas, evitando así la amputación de la extremidad. Por el contrario, en los casos sintomáticos el tratamiento endovascular o quirúrgico puede ser apropiado, especialmente si un aneurisma o trombosis arterial están presentes 4,5 . No hay consenso sobre la mejor terapia para esta entidad, y los tratamientos deben ser seleccionados para cada caso específico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En Chile, se describió el caso de un aneurisma de la arteria ciática persistente, en el cual ligaron el vaso y resecaron el aneurisma por abordaje glúteo transmuscular, sin restablecer el flujo ni interponer injertos, notándose signos de isquemia aguda inmediata durante la intervención quirúrgica 27 . El paciente, finalmente, tuvo una buena evolución.…”
Section: Discussionunclassified